THE ORIGIN OF THE PREECLAMPSIA AND ECLAMPSIA: PLACENTATION - Pacora Portella, Percy (2015)
Preeclampsia and eclampsia cause significant morbidity and mortality for mothers and neonates in Peru. Recent studies have suggested that secretion excess of a naturally occurring anti-angiogenic molecule of placental origin (soluble fmslike tyrosine kinase-1 - sFlt-1, or sVEGFR-1) may contribute to the pathogenesis of preeclampsia. sFlt-1 acts by antagonizing two pro-angiogenic molecules –vascular endothelial growth factor (VEGF) and placental growth factor (PLGF). Abnormalities in the angiogenic balance have been proposed as having a major role in the molecular cascade leading to proteinuria, hypertension, and endothelial dysfunction. Further evidence supports the hypothesis that angiogenic balance is crucial for differentiation and invasion of cytotrophoblasts. The abnormal placentation and the accompanying hypoxia may, in turn, result in more sFlt-1 production, thus leading to a vicious cycle of sFlt-1 production, eventually causing preeclampsia. Preeclampsia and eclampsia are clinical manifestations of vascular disease of pregnancy and this disease occurs because of the involvement of genetic and environmental factors: anatomic, hereditary, nutritional, nflammatory, physical and chemical contamination, metabolic, emotional and social. The clinical picture of the syndrome reflects the endothelial damage at the maternal/fetal compartment. Arterial hypertension and proteinuria may be absent before the eclamptic convulsion. Placenta study is mandatory to establish the diagnosis of vascular damage in pregnancy. The severity of the vascular lesion in preeclampsia is assessed according to maternal and perinatal birth outcomes.